DEGRADATION EFFICIENCY OF PHENOLIC COMPOUNDS USING IMMOBILIZED PEROXIDASE PURIFIED FROM SOYBEAN - & Aziz, Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed on purification, immobilization and application of peroxidase enzyme from whole plant of soy bean for the decolorization of textile dyes and degradation of some phenolic compounds. The purification of peroxidase was in two steps include: concentration by sucrose and gel filtration by using sephadex G-150. The purification fold was 4.46 and 2.09 with an enzyme yield of 22.34% and 25.55% for peak 1 and peak 2 respectively. The purified peroxidase enzyme was immobilized by two methods include: covalent linkage immobilization by gluteraldehyde activated chitosan and entrapment by sodium alginate and agarose gel, the immobilization ratio reached to 58.07%, 50% and 11.75% respectively. Crude, purified and immobilized peroxidase were studied with textile dyes (red, blue, yellow and black) after 24 hr, the maximum removal efficiency was with immobilized peroxidase reached to 13.25, 35.12, 14.37 and 26.92 % respectively. Immobilized peroxidase on chitosan was able to degrade some phenolic compounds (tannic acid, naphthalene and gallic acid) during 2 hr, and the degradation efficiency was reached to 95.85%, 79.75% and 33.88% respectively.